"Homerocentony" jako najbardziej skrajna próba hellenizacji chrześcijaństwa - Gilski, Marek (Verbum Vitae, 2021)
This article presents and evaluates one of the attempts to Hellenize Christianity. It concerns the Homerocentos, works written in Christian circles from the 4th century onwards, which convey the message of the Gospel almost exclusively using the vocabulary of the Iliad and the Odyssey. The text includes a discussion of the technique of creating these works, their content, form, and theology. The analysis of Homerocentos leads to the following conclusions: a) it is impossible to understand and properly interpret Christianity without the knowledge of Homeric poems; b) the Gospel is only a new interpretation of the Iliad and the Odyssey; c) Christianity does not bring new content, but only organizes what is available in culture.